Clarifying the role of ATOH7 in glaucoma endophenotypes. Issue 4 (23rd January 2014) - Venturini, Cristina; Nag, Abhishek; Hysi, Pirro G; Wang, Jie Jin; Wong, Tien Y; Healey, Paul R; Mitchell, Paul; Hammond, Christopher J; Viswanathan, Ananth C; ,
Abstract : Background/aims: The ATOH7 gene has been previously associated with glaucoma and glaucoma-related traits, such as disc size and cup/disc ratio (CDR). CDR is an important part of the glaucoma phenotype, whereas the relationship between the disc size and the disease is not well understood. The aim of this study was to investigate whether ATOH7 is associated independently with CDR or merely with the size of the optic disc. Method: We carried out an association analysis for a candidate region, including ATOH7 for two populations: the Blue Mountains Eye Study and the TwinsUK cohort. We performed three linear regression models for (1) disc size adjusted on age, sex and intraocular pressure (IOP), (2) CDR adjusted on age, sex and IOP and (3) CDR adjusted on age, sex, IOP and disc size. Results: A strong signal was found at rs7916697 for disc size. This single nucleotide polymorphism (SNP) was also associated with CDR adjusted on age, sex and IOP. However, this SNP was not associated with CDR when adjusted on age, sex, IOP and also disc size. Conclusions: This study finds that ATOH7 is associated with optic disc size but not independently with CDR.